Rhodolith density increases the bioavailability of sedimentary organic matter and meiofauna biodiversity - Martins Neto, João (2020)
Rhodolith beds increase complexity of the seabed and are hotspot of biodiversity. Despite the several crucial ecosystem services provided by the rhodoliths, they are still threatened by global change and local anthropogenic impacts. In this study, conducted on one of the largest beds of calcareous algae in the world located on the continental shelf of Espírito Santo state, eastern Brazil, we test whether higher complexity of seabed could explain spatial biodiversity patterns of marine meiofauna and Nematoda. Our results showed that the sedimentary habitat of the sites containing high density of rhodoliths presented higher concentrations of labile fraction of organic matter available to benthic consumers through remineralization. The higher retention and quality of the organic material, as showed by biopolymeric carbon and concentration of protein, supported higher diversity, abundance, and biomass of free-living nematodes supporting the study hypothesis. The results of this study showed that the loss rhodolith beds or even decrease in density of calcareous nodules by human impacts will result in a significant loss of biodiversity and, this a range of ecosystem services they provide.